The effects of clinical and pharmacological factors on the ratio of clozapine to norclozapine in psychiatric patients - Mach, Anna; Wnorowska, Anna; Siwek, Marcin; Wojnar, Marcin; Radziwoń-Zaleska, Maria (Frontiers in Pharmacology, 2025)
BackgroundDue to its exceptional effectiveness, clozapine (CLO), whose metabolite is norclozapine (NCLO), is a drug of choice in the management of treatment-resistant schizophrenia. The purpose of this study was to assess the factors modifying the CLO/NCLO ratio (CNR).MethodsA total of 446 blood samples (233 of which were drawn from females and 213 from males, aged from 18 to 77 years) were analyzed in this study. The patients were treated at a psychiatric hospital in the period 2016–2021. Serum CLO and NCLO levels were determined with high-performance liquid chromatography coupled with a UV detector.ResultsThe median CNR was 2.38 (minimum 0.30, maximum 14.36). Our analysis showed that neither sex (p= 0.135) nor smoking (p = 0.774) had any significant effect on the CNR. However, increased doses of CLO resulted in lower CNR values (p = 0.005). Concomitant use of other psychotropic drugs increased the CNR (p = 0.001).DiscussionThe results of our study indicate a need for personalized CLO treatment. Assessing the CNR may be useful in identifying CLO interaction with other psychotropic drugs.